Public Disclosure and Bank Failures - Levy Yeyati, Eduardo (IMF Working Papers; Working Paper ;, 1997)
This paper examines how public disclosure of banks' risk exposure affects banks' risk-taking incentives and assesses how the presence of informed depositors influences the soundness of the banking system. It finds that, when banks have complete control over the volatility of their loan portfolios, public disclosure reduces the probability of banking crises. However, when banks do not control their risk exposure, the presence of informed depositors may increase the probability of bank failures.